Role of Religious Immortology Ideas in Formation of Consciousness of Modern Ukrainian Youth - Anatoly Val’chuk (Pedagogical Discourse, 2012)
The research is devoted to consideration of religious immortology meaning in formation of consciousness of youth. The role of immortology ideas in life of the people is shown. Special attention is paid to their specific influence on life of modern Ukrainian youth